2017
DOI: 10.1038/s41467-017-01048-8
|View full text |Cite
|
Sign up to set email alerts
|

Kif2 localizes to a subdomain of cortical endoplasmic reticulum that drives asymmetric spindle position

Abstract: Asymmetric positioning of the mitotic spindle is a fundamental process responsible for creating sibling cell size asymmetry; however, how the cortex causes the depolymerization of astral microtubules during asymmetric spindle positioning has remained elusive. Early ascidian embryos possess a large cortical subdomain of endoplasmic reticulum (ER) that causes asymmetric spindle positioning driving unequal cell division. Here we show that the microtubule depolymerase Kif2 localizes to this subdomain of cortical E… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 65 publications
1
23
0
Order By: Relevance
“…KIF2 is a kinesin-like transcription factor that is expressed in various tissues, and is implicated in the regulation of inflammation, cell apoptosis and other physiological processes. 7,13 In the present study, we found that KIF2 expression is aberrantly…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…KIF2 is a kinesin-like transcription factor that is expressed in various tissues, and is implicated in the regulation of inflammation, cell apoptosis and other physiological processes. 7,13 In the present study, we found that KIF2 expression is aberrantly…”
Section: Discussionsupporting
confidence: 57%
“…KIF2 is a kinesin‐like transcription factor that is expressed in various tissues, and is implicated in the regulation of inflammation, cell apoptosis and other physiological processes . Dysregulation of KIF2 expression has been identified to be associated with various pathological progression .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Drosophila male germline stem cells, generating an equal sized gonialblast and a self-renewed germline stem cell (Spradling et al, 2011), control spindle symmetry with the centrosomalassociated microtubule depolymerizing kinesin Klp10A (Kinesin 13 family); klp10A mutants contain unequal sized centrosomes, resulting in the formation of asymmetric spindles and unequal sized cell divisions (Chen et al, 2016). Similarly, ER localized Kif2A, a microtubule depolymerase, induces spindle asymmetry and positioning in ascidians (Costache et al, 2017). Since the anaphase spindle is the primary determinant for the positioning of the cleavage furrow (D'Avino et al, 2015;Glotzer, 2017;Green et al, 2012;Rappaport, 1986), spindle geometry can at least partially explain physical asymmetry.…”
Section: Introductionmentioning
confidence: 99%